Healthy human development across the lifespan: adult development and aging - Touch Mercer, Gina (Henry Stewart Talks, 2023)
Behavioral medicine, Theories of human development, Classification of human development stages, Emerging adulthood, Middle adulthood, older adulthood, Healthy aging, Lifestyle behaviors, Resilience, character traits, and virtues